(untitled) (Nordic Journal of African Studies, 2003)
Studies on linguistic human rights in various parts of the globe are now in vogue. The present paper analyses the language policy and practice in Kenya so as to determine the extent to which language rights are observed. The analyses focus on language use both in private and public domains. It turns out that to a large extent the language rights are upheld. However, some degree of infringement is noted both in the private and public levels of language use. It is shown that what constitutes a breach of language rights at the private level is largely "voluntary". The article calls for a balancing act from the language planners and policy implementers so that a higher level of language rights for enhanced democracy is realised.